Mineral crystal active material
By optimizing the preparation process of tuff matter slate, mineral crystal active energy materials with particle sizes of 1-5 microns were prepared, which solved the side effects of chemical additives in cosmetics and nursing supplies, and achieved efficient and stable skin care effects and low cost. Production, suitable for all skin types.
Patent Information
- Application Number
- CN202411186683.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2024-12-13
AI Technical Summary
The commonly used chemical additives in traditional cosmetics and nursing products have side effects, and the preparation process of ore crystal active materials is complex, with high cost and unstable active ingredients, making it difficult to meet the market's demand for natural, safe and efficient materials.
By crushing, sieving, calcining, water quenching, pickling, water washing and grinding, ore crystal active energy materials with particle sizes of 1-5 microns are prepared to remove impurities and improve activity and stability. in cosmetics and care products.
It provides natural, safe and efficient mineral crystal active energy materials, which significantly improves skin care effects, is suitable for all skin types, reduces production costs, and is in line with the concept of sustainable development.
Abstract
Description
Technical Field
[0001] The invention relates to a mineral crystal active energy material and a preparation method thereof, in particular to a mineral crystal active energy material prepared from tuffaceous slate and application thereof in cosmetics and care products. Background Art
[0002] Tuffaceous slate is a sedimentary rock mainly composed of tuffaceous and clay minerals, with a good layered structure and certain plasticity. Due to its unique physical and chemical properties, tuffaceous slate has a wide range of application prospects in the industrial field. In recent years, with the development of materials science, people have begun to explore the transformation of tuffaceous slate into materials with specific functions to meet the needs of different industries.
[0003] In the cosmetics and skin care products industry, consumers have higher and higher requirements for product efficacy. Traditional cosmetics and skin care products rely on chemical additives to achieve specific skin care effects, but these chemical ingredients often have certain side effects. Therefore, the development of a natural, safe and efficient active material has become a trend in the industry. Mineral crystal active energy materials, with their unique physical and chemical properties, can meet this market demand.
[0004] Although tuffaceous slate has the potential to be converted into mineral active materials, its conversion process faces many challenges. First, the composition of tuffaceous slate is complex and contains a variety of organic and inorganic impurities, the presence of which will affect the purity and activity of the final product. Secondly, the particle size and structure of tuffaceous slate need to be finely adjusted to meet the specific specifications required for cosmetics and care products. In addition, traditional preparation methods often have high energy consumption and low efficiency, which does not conform to the sustainable development concept of modern industrial production.
[0005] At present, there are some mineral-based active materials on the market, but most of these materials have the following limitations: first, the preparation process is complicated and the cost is high; second, the stability of the active ingredients is insufficient and it is difficult to maintain for a long time; third, it is highly irritating to the skin and is not suitable for sensitive skin. Therefore, it is particularly urgent to develop a mineral crystal active energy material with a simple preparation process, low cost, high activity and skin-friendly. Summary of the invention
[0006] The present invention provides a mineral crystal active energy material prepared from tuffaceous slate and a preparation method thereof. The mineral crystal active energy material not only has excellent physical and chemical properties, but also performs well in application in cosmetics and care products, can significantly improve the skin care effect of the product, while maintaining the naturalness and safety of the product.
[0007] The technical solution adopted by the present invention is: the mineral crystal active energy material is prepared from tuffaceous slate, and the preparation method of the mineral crystal active energy material comprises the following steps:
[0008] Step 1: crushing the tuffaceous slate, then screening the crushed tuffaceous slate particles, and selecting particles with a particle size between 30-50 meshes as raw materials;
[0009] Step 2: placing the screened tuffaceous slate particles into a high-temperature furnace for calcining to fully decompose the organic matter and volatile substances in the tuffaceous slate;
[0010] Step 3: After calcination, the calcined tuffaceous slate particles are subjected to water quenching to form a porous structure on the surface, thereby increasing its specific surface area and activity;
[0011] Step 4: acid-washing the tuffaceous slate particles after water quenching to remove surface impurities and residual organic matter;
[0012] Step 5: Put the acid-washed tuffaceous slate particles into clean water for thorough washing to remove residual acidic substances and ensure the purity of the material;
[0013] Step 6: Place the washed tuffaceous slate particles into a drying oven for drying to remove excess water and ensure the stability of the material;
[0014] Step 7: Grind the dried tuffaceous slate particles to obtain ultrafine mineral crystal active energy materials with a particle size of 1-5 microns.
[0015] As a further improvement of the present invention, in step one, the crushing equipment is a jaw crusher or a hammer crusher. After crushing, the particles are classified according to particle size through screening equipment, and particles with a particle size between 30-50 mesh are selected as raw materials.
[0016] As a further improvement of the present invention, in the step 2, the calcination temperature of the high temperature furnace is controlled between 800-1000° C., and the calcination time is between 2-4 hours.
[0017] As a further improvement of the present invention, in step three, the water quenching treatment is to quickly immerse the calcined tuffaceous slate particles in cold water, and use the principle of thermal expansion and contraction to form a porous structure on the particle surface.
[0018] As a further improvement of the present invention, in step 4, pickling is carried out using dilute hydrochloric acid with a concentration between 5% and 10%, the pickling time is between 1 and 2 hours, and continuous stirring is required during the pickling process, and the stirring speed is 50-120 rpm.
[0019] As a further improvement of the present invention, in step five, the washing with clean water is carried out continuously, and the pH value of the washing liquid needs to be monitored during the washing process until the pH value of the washing liquid reaches neutral.
[0020] As a further improvement of the present invention, in step six, the temperature in the drying box is controlled between 100-150° C., and the drying time is between 4-8 hours.
[0021] As a further improvement of the present invention, in step seven, the grinding equipment is one of a ball mill, a vibration mill, and a jet mill.
[0022] The application of the above-mentioned mineral crystal active energy material is used in cosmetics and care products.
[0023] As a further improvement of the present invention, the cosmetics include face cream, lotion, face mask, and face cleanser, wherein the amount of the mineral crystal active material added is 2-6% of the total mass of the product, and the tiny particles of the mineral crystal active material can penetrate into the skin pores, promote the skin to absorb the effective ingredients in the cosmetics, and release minerals at the same time, help the skin maintain water and oil balance, and enhance the elasticity and luster of the skin;
[0024] The care products include shampoo, conditioner, and shower gel, wherein the added amount of mineral crystal active energy material is 2-6% of the total mass of the product. The mineral crystal active energy material can improve the surface state of hair and skin, enhance the luster and smoothness of hair, and provide necessary minerals for the skin, achieving the effect of deep nourishment and repair.
[0025] The beneficial effects of the present invention are as follows:
[0026] (1) By using tuffaceous slate as a raw material, the present invention provides a natural, environmentally friendly mineral crystal active energy material, avoiding the side effects that may be caused by chemical additives and meeting consumers' demand for natural and safe products.
[0027] (2) The preparation method of the present invention effectively removes impurities in tuffaceous slate through fine crushing, calcining, water quenching, pickling, water washing, drying and grinding steps, ensuring the high purity and high activity of the mineral crystal active material, thereby improving the efficacy of cosmetics and care products.
[0028] (3) The mineral crystal active energy material of the present invention has good stability and can maintain its active ingredients for a long time, ensuring the consistency of the product's effects during storage and use; at the same time, the mineral crystal active energy material has low irritation to the skin and is suitable for all skin types, especially sensitive skin, thus broadening the scope of application of the product.
[0029] (4) The particle size of the mineral crystal active energy material of the present invention is controlled at 1-5 microns, so that it has excellent dispersibility and permeability in cosmetics and care products, can penetrate deep into the skin, exert better skin care effects, enhance skin elasticity and luster, and provide deep nourishment and repair for hair, meeting consumers' demand for high-quality life.
[0030] (5) The preparation method of the present invention has low energy consumption and high efficiency, which is in line with the sustainable development concept of modern industrial production, and is conducive to reducing production costs and improving market competitiveness. DETAILED DESCRIPTION
[0031] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0032] The present invention provides a mineral crystal active energy material, which is prepared from tuffaceous slate. The preparation method of the mineral crystal active energy material comprises the following steps:
[0033] Step 1: crushing the tuffaceous slate, and then screening the crushed tuffaceous slate particles, selecting particles with a particle size between 30-50 mesh as raw materials, wherein the crushing equipment is one of a jaw crusher and a hammer crusher, and after crushing, the particles are classified according to the particle size through a screening equipment, and the particles with a particle size between 30-50 mesh are selected as raw materials;
[0034] Step 2: Place the screened tuffaceous slate particles into a high-temperature furnace for calcination to fully decompose the organic matter and volatile substances in the tuffaceous slate, wherein the calcination temperature of the high-temperature furnace is controlled between 800-1000°C and the calcination time is between 2-4 hours;
[0035] Step 3: After calcination, the calcined tuffaceous slate particles are subjected to water quenching treatment to form a porous structure on the surface, thereby increasing its specific surface area and activity. The water quenching treatment is to quickly immerse the calcined tuffaceous slate particles in cold water to form a porous structure on the particle surface by utilizing the principle of thermal expansion and contraction;
[0036] Step 4: pickling the tuffaceous slate particles after water quenching to remove surface impurities and residual organic matter, wherein the pickling is carried out with dilute hydrochloric acid with a concentration of 5%-10% and a pickling time of 1-2 hours, and continuous stirring is required during the pickling process at a stirring speed of 50-120 rpm;
[0037] Step 5: Put the acid-washed tuffaceous slate particles into clean water for thorough washing to remove residual acidic substances and ensure the purity of the material. The clean water washing is carried out continuously, and the pH value of the washing liquid needs to be monitored during the washing process until the pH value of the washing liquid reaches neutral;
[0038] Step 6: Put the washed tuffaceous slate particles into a drying oven for drying to remove excess water and ensure the stability of the material. The temperature in the drying oven is controlled between 100-150°C and the drying time is between 4-8 hours.
[0039] Step seven: Grind the dried tuffaceous slate particles to obtain ultrafine mineral crystal active energy materials with a particle size of 1-5 microns, wherein the grinding equipment is one of a ball mill, a vibration mill, and a jet mill.
[0040] The application of the above-mentioned mineral crystal active energy material is characterized in that the mineral crystal active energy material is applied to cosmetics and care products. The cosmetics include face creams, lotions, facial masks, and facial cleansers, wherein the amount of mineral crystal active energy material added is 2-6% of the total mass of the product, and the tiny particles of the mineral crystal active energy material can penetrate into the skin pores, promote the skin to absorb the effective ingredients in the cosmetics, and release minerals at the same time, help the skin maintain water and oil balance, and enhance the elasticity and luster of the skin; the care products include shampoo, conditioner, and shower gel, wherein the amount of mineral crystal active energy material added is 2-6% of the total mass of the product, and the mineral crystal active energy material can improve the surface state of hair and skin, enhance the luster and smoothness of hair, and provide the skin with necessary minerals at the same time, achieving the effect of deep nourishment and repair.
[0041] Example:
[0042] This embodiment provides a method for preparing a mineral crystal active energy material, and the specific steps are as follows.
[0043] (1) The tuffaceous slate is crushed by using a jaw crusher to crush large pieces of tuffaceous slate into particles with a size between 30 and 50 meshes; after crushing, the particles are classified according to the particle size by a vibrating screening machine, and particles with a uniform particle size of 30 to 50 meshes are selected as raw materials.
[0044] (ii) placing the screened tuffaceous slate particles into a high-temperature furnace for calcining; the calcining temperature is controlled at 900° C. and the calcining time lasts for 3 hours to ensure that the organic matter and volatile substances in the tuffaceous slate are fully decomposed.
[0045] (iii) After calcination is completed, the calcined tuffaceous slate particles are quickly immersed in cold water for water quenching. After water quenching, a porous structure is formed on the surface of the particles, and the specific surface area and activity are significantly improved.
[0046] (iv) pickling the tuffaceous slate particles after water quenching; using dilute hydrochloric acid with a concentration of 7% for pickling for 1.5 hours, stirring continuously during the pickling to ensure uniform pickling; after pickling, impurities and residual organic matter on the surface of the particles are effectively removed.
[0047] (V) The acid-washed tuffaceous slate particles are placed in clean water for thorough washing until the pH value of the washing liquid reaches neutral; the washing process lasts for about 2 hours to ensure the purity of the material.
[0048] (6) The washed tuffaceous slate particles are placed in a drying box for drying; the drying temperature is set at 120° C. and the drying time is continued for 6 hours to remove excess moisture and ensure the stability of the material.
[0049] (VII) Grinding the dried tuffaceous slate particles and using a ball mill for ultrafine grinding to obtain mineral crystal active energy materials with a particle size of 1-5 microns.
[0050] Experiment 1:
[0051] In order to verify the application effect of the mineral crystal active energy material of the present invention in cosmetics, the present application conducted the following experiments:
[0052] Experimental materials: mineral crystal active energy material prepared in the examples and commercially available common facial cream.
[0053] Experimental method: (1) Add the mineral crystal active energy material prepared in the example to the face cream at an addition amount of 3%, stir well to prepare the face cream of the experimental group;
[0054] (2) A commercially available ordinary facial cream of the same brand and model was selected as a control group;
[0055] (3) 20 female volunteers aged between 25 and 36 were selected and divided into two groups, with 10 people in each group. They were given the experimental group and the control group facial cream, respectively, once in the morning and once in the evening for 18 consecutive days.
[0056] (4) The skin moisture content, oil content, elasticity and glossiness of the volunteers were measured before the experiment, on the 14th day and the 28th day.
[0057] Experimental results:
[0058] (1) On the 14th day of the experiment, the skin moisture content of the volunteers who used the experimental group cream increased by an average of 15%, while the skin moisture content of the volunteers who used the control group cream increased by only 5%.
[0059] (2) On the 28th day of the experiment, the volunteers who used the experimental group cream had an average decrease in skin oil content of 10%, an increase in skin elasticity of 20%, and an increase in glossiness of 18%. The volunteers who used the control group cream had an average decrease in skin oil content of 5%, an increase in skin elasticity of 10%, and an increase in glossiness of 10%.
[0060] (3) After the experiment, the volunteers in the experimental group said that their skin felt more comfortable after using the cream, and the effect was significantly better than that of the control group.
[0061] Experiment 2:
[0062] In order to verify the application effect of the mineral crystal active energy material of the present invention in care products, the present application conducted the following experiments:
[0063] Experimental materials: mineral crystal active energy material prepared in the examples and commercially available ordinary shampoo.
[0064] Experimental method: (1) Add the mineral crystal active energy material prepared by the present invention into shampoo at an addition amount of 4%, stir well and evenly to prepare the experimental group shampoo;
[0065] (2) Take a commercially available ordinary shampoo of the same brand and model as a control group;
[0066] (3) Twenty volunteers aged between 20 and 40 were selected and divided into two groups, with 10 people in each group. They were washed with the experimental group shampoo and the control group shampoo three times a week for one month.
[0067] (4) The volunteers’ hair gloss, smoothness, and scalp health were evaluated before the experiment, on the 15th day, and on the 30th day.
[0068] Experimental results:
[0069] (1) On the 15th day of the experiment, the volunteers who used the experimental shampoo had an average hair glossiness increase of 25%, smoothness increase of 20%, and scalp health improvement; while the volunteers who used the control group shampoo had a hair glossiness increase of 10%, smoothness increase of 10%, and no significant improvement in scalp health improvement.
[0070] (2) On the 30th day of the experiment, the volunteers who used the experimental shampoo had an average hair glossiness increase of 35%, smoothness increase of 30%, and further improvement in scalp health, with less dandruff and more balanced oil secretion. The volunteers who used the control group shampoo had a hair glossiness increase of 15%, smoothness increase of 20%, and improvement in scalp health, but the effect was not as significant as that of the experimental group.
[0071] (3) After the experiment, volunteers in the experimental group generally reported that their hair became shinier and smoother, and their scalp felt more comfortable after using the experimental shampoo, and the effect was significantly better than that of the control group.
[0072] It can be seen from the above experiments 1 and 2 that the mineral crystal active energy material prepared by the examples shows significant improvement effects in the application of cosmetics and care products. In cosmetics, it can effectively increase the moisture content of the skin, reduce the oil content, and enhance the elasticity and glossiness of the skin; in care products, it can significantly increase the glossiness and smoothness of the hair, while improving the health of the scalp. Therefore, the mineral crystal active energy material has a wide range of application prospects and can bring new breakthroughs to the cosmetics and care products industry.
[0073] In summary, the present invention provides an innovative mineral crystal active energy material and a preparation method thereof, which not only solves the problems caused by chemical additives in traditional cosmetics and care products, but also improves the performance and market competitiveness of the product by optimizing the preparation process, and has significant economic and social benefits.
[0074] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. Mineral crystal active energy material, prepared from tuffaceous slate, characterized in that: The preparation method of the mineral crystal active energy material comprises the following steps: Step 1: crushing the tuffaceous slate, then screening the crushed tuffaceous slate particles, and selecting particles with a particle size between 30-50 meshes as raw materials; Step 2: placing the screened tuffaceous slate particles into a high-temperature furnace for calcining to fully decompose the organic matter and volatile substances in the tuffaceous slate; Step 3: After calcination, the calcined tuffaceous slate particles are subjected to water quenching to form a porous structure on the surface, thereby increasing its specific surface area and activity; Step 4: acid-washing the tuffaceous slate particles after water quenching to remove surface impurities and residual organic matter; Step 5: Put the acid-washed tuffaceous slate particles into clean water for thorough washing to remove residual acidic substances and ensure the purity of the material; Step 6: Place the washed tuffaceous slate particles into a drying oven for drying to remove excess water and ensure the stability of the material; Step 7: Grind the dried tuffaceous slate particles to obtain ultrafine mineral crystal active energy materials with a particle size of 1-5 microns.
2. The mineral crystal active energy material according to claim 1, characterized in that: In the step 1, the crushing equipment is a jaw crusher or a hammer crusher. After crushing, the particles are classified according to particle size through a screening device, and particles with a particle size between 30-50 mesh are selected as raw materials.
3. The mineral crystal active energy material according to claim 1, characterized in that: In the step 2, the calcination temperature of the high temperature furnace is controlled between 800-1000° C., and the calcination time is between 2-4 hours.
4. The mineral crystal active energy material according to claim 1, characterized in that: In the step three, the water quenching treatment is to quickly immerse the calcined tuffaceous slate particles in cold water, and use the principle of thermal expansion and contraction to form a porous structure on the surface of the particles.
5. The mineral crystal active energy material according to claim 1, characterized in that: In the step 4, the pickling is carried out with dilute hydrochloric acid, the concentration of which is between 5% and 10%, the pickling time is between 1 and 2 hours, and continuous stirring is required during the pickling process, and the stirring speed is 50 to 120 revolutions per minute.
6. The mineral crystal active energy material according to claim 1, characterized in that: In the step 5, the washing with clean water is carried out continuously, and the pH value of the washing liquid needs to be monitored during the washing process until the pH value of the washing liquid reaches neutral.
7. The mineral crystal active energy material according to claim 1, characterized in that: In step six, the temperature in the drying box is controlled between 100-150° C., and the drying time is between 4-8 hours.
8. The mineral crystal active energy material according to claim 1, characterized in that: In the step 7, the grinding equipment is one of a ball mill, a vibration mill and a jet mill.
9. The use of the mineral crystal active energy material according to any one of claims 1 to 8, characterized in that: The mineral crystal active energy material is used in cosmetics and care products.
10. The use of the mineral crystal active energy material according to claim 9, characterized in that: The cosmetics include face creams, lotions, face masks, and face cleansers, wherein the amount of the mineral crystal active material added is 2-6% of the total mass of the product. The tiny particles of the mineral crystal active material can penetrate deep into the skin pores, promote the skin to absorb the active ingredients in the cosmetics, and release minerals at the same time, helping the skin maintain water and oil balance and enhancing the elasticity and luster of the skin; The care products include shampoo, conditioner, and shower gel, wherein the added amount of mineral crystal active energy material is 2-6% of the total mass of the product. The mineral crystal active energy material can improve the surface state of hair and skin, enhance the luster and smoothness of hair, and provide necessary minerals for the skin, achieving the effect of deep nourishment and repair.
